Risk factors for increased transaminase enzymes in children with epilepsy using valproic acid - Sari, Ina Julia; Anidar, Anidar; Akbar, Zaki; Yusuf, Sulaiman; Bakhtiar, Bakhtiar; Ismy, Jufitriani (Paediatrica Indonesiana, 2026)
Background Valproic acid (VPA) is a commonly used first-line medication for generalized epilepsy. Hepatotoxicity, manifested by elevations in transaminase enzymes, is a serious, life-threatening adverse effect of VPA use. Objective To determine the prevalence and risk factors for elevated transaminase enzymes in children with epilepsy receiving VPA. Methods A cross-sectional study was conducted at Zainoel Abidin General Hospital, Banda Aceh, Indonesia on 50 children with epilepsy aged 1 month to 18 years who received VPA and experienced elevations in serum aspartate aminotransferase (AST) and/or alanine aminotransferase (ALT). We compared clinical characteristics Results  Of 294 children with epilepsy, 50 children (17%) met the study criteria. Elevated AST was found in 31 (62%) subjects and elevated ALT in 35 (70%) subjects. Bivariate analysis revealed a significant negative association between elevated AST and duration of treatment (OR=0.925; P=0.044) and a positive association between elevated ALT and number of antiepileptic drugs (AEDs) received (OR=7.691; P=0.022). Nutritional status was significantly associated with elevated ALT (OR=0.412; P=0.041). Multivariate analysis showed that the number of AEDs was he only significant risk factor for elevated AST (OR=4.663; P=0.040), and VPA dose was the most significant only significant factor for elevated ALT (OR=1.183; P=0.029). Conclusion In children receiving VPA for the treatment of epilepsy, the number of AEDs received is a risk factor for elevated ALT, while VPA dose is a risk factor for elevated AST.